Reflections on Interpretation Training from an Ecological Perspective in the Context of “Internet Plus” - Chen, Shengbai; Luo, Haiyan; Wu, Jiaodi (Pacific International Journal, 2024)
A scientific interpretation training model is the foundation of interpretation teaching. This article examines interpretation training research in the context of “Internet plus” from the perspective of eco-translatology, focusing on the guiding role of ecological translation theory in current interpretation training research, and attempts to construct an ecological interpretation teaching model from four dimensions, namely, “Learning with Purpose”, “Translating with Intent”, “Researching with Impact”, and “Evaluating with Purpose”, according to the unique interdisciplinary nature, multiple dynamics, and sustainability of ecological translatology, in order to achieve the scientific and diversified teaching of interpreting in China. By embracing both virtual and physical environments, interpretation training can adapt to the evolving landscape of the digital age while preserving the essence of effective communication.